2023
DOI: 10.1021/acs.jpca.3c01362
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Latent Space Simulators for Distributed and Multimolecular Trajectories

Abstract: All atom molecular dynamics (MD) simulations offer a powerful tool for molecular modeling, but the short time steps required for numerical stability of the integrator place many interesting molecular events out of reach of unbiased simulations. The popular and powerful Markov state modeling (MSM) approach can extend these time scales by stitching together multiple short discontinuous trajectories into a single long-time kinetic model but necessitates a configurational coarse-graining of the phase space that en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…[ 110,111 ] Therefore, some alternative approaches to MSM have been proposed, such as methods based on latent space simulators. [ 112,113 ] This method uses three different deep learning architectures, which involve encoding molecular trajectories into a latent space, propagating low‐dimensional trajectories within this latent space, and decoding the latent space back to configuration space, to train on short, discontinuous trajectories and multiple‐molecule systems for trajectory prediction. Additionally, some studies have attempted to learn dynamic processes based on recurrent neural network.…”
Section: Machine Learning In Simulationsmentioning
confidence: 99%
“…[ 110,111 ] Therefore, some alternative approaches to MSM have been proposed, such as methods based on latent space simulators. [ 112,113 ] This method uses three different deep learning architectures, which involve encoding molecular trajectories into a latent space, propagating low‐dimensional trajectories within this latent space, and decoding the latent space back to configuration space, to train on short, discontinuous trajectories and multiple‐molecule systems for trajectory prediction. Additionally, some studies have attempted to learn dynamic processes based on recurrent neural network.…”
Section: Machine Learning In Simulationsmentioning
confidence: 99%
“…In addition, the size and complexity of molecular dynamics or DFT simulation trajectories often pose a barrier to their analysis and are often overlooked or neglected. However, recent advances like the Grisanov Reweighting Enhanced Sampling Technique (GREST), Latent Space Simulators (LSS), and contributions by Vacher et al through Bayesian neural networks have shown potential to convert simulation trajectories into machine friendly and physically meaningful inputsenhancing collective variable discovery, configuration sampling, and property estimation . Although these methods have been applied to macromolecules as large as pentapeptides, their application to larger polymeric materials has not been explored.…”
Section: Introduction To Conjugated Polymer Representation and Ai/ml ...mentioning
confidence: 99%
“…[31][32][33][34] DDMD is a deep learning-driven MD simulation technique that avoids the problems outlined above by finding undersampled states from an ensemble of running simulations without requiring the user to define a set of physical CV(s). 35,36 It does so by learning a lowdimensional latent representation [37][38][39] of the simulation data on the fly and treating it as a proxy for the CV. DDMD has recently been shown to enhance the conformational sampling of proteins and protein-ligand complexation.…”
Section: Introductionmentioning
confidence: 99%